Exchange Rate and Output Fluctuations in the Small Open Economy of Mauritius - Bastos, Fabiano; Angelo Divino, Jose (2012)
The authors estimate a VAR and compute generalized impulse response to analyze the joint dynamics of four key macroeconomic variables in the small open economy of Mauritius. Results suggest that nominal exchange rate and interest rate have limited ability to impact output growth over the medium-run. Large error bands hinder analysis of the inflation output trade-off, but evidence points to a weak relationship in the short run as well. These findings are used to shed some light into the policy response to the current worldwide economic slowdown affecting Mauritius.